Evaluation Study of the High Yielding Varieties Programme Volume - II - Planning Commission (Planning Commission, 1969)
"In the year 1967-68 the FEO carried out detailed studies on the implementation of the High Yielding Varieties Programme. For the kharif,1 967 two reports were brought out in march and August, 1968. For the Rabi,1967-68 a separate report for wheat was prepared in October,1968. This report forms part of our Rabi enquiry of the last year covering paddy and jowar crops. The study for paddy and jowar was carried out in 14 development blocks (10 paddy, 4 jowar) in 8 States. These sample blocks were the same as studied in the kharif season; but this season's enquiry was confined only to such blocks where the coverage of area was significant. The analysis in this report is on the same pattern followed in our earlier reports and covers all the major aspects of the programme. However, one distinct feature in this analysis is the comparison of the levels of adoption of improved practices, cultivation expenses and yields as between the kharif and Rabi seasons."
Report For The Rabi 1967-68 —Paddy & Jowar